PENGAWASAN TERHADAP KEPATUHAN PEMBAYARAN PAJAK DAERAH YANG DIPUNGUT MELALUI SISTEM SELF-ASESSMENT - Rai Mantili; Putu Eka Trisna Dewi (Jurnal Aktual Justice, 2019)
Local tax collection in Indonesia is carried out using the Official Assessment system and the Self-Assessment system. In the Self-Assessment system, all tax obligations are fulfilled by the taxpayer, Fiskus only supervises through audit procedures. The implementation of tax collection with this system really requires taxpayer compliance so that it is necessary to monitor the taxpayer's compliance. This raises problems regarding how to monitor compliance with the payment of local taxes collected through the self-assessment system. This paper uses a normative research method with a statutory approach and a legal conceptual approach. This paper concludes that the supervision of taxpayer compliance in paying taxes with a self-assessment system is carried out by examining taxpayers. The authority of the regional head to conduct audits and the obligation of taxpayers to cooperate in undergoing the examination is regulated in Article 170 of the Regional Tax and Retribution Act. The results of the tax audit are recorded in the audit report. Enforcement of regional tax law against taxpayers who do not comply begins with submitting a warning letter, if the warning letter is not heeded, it will be subject to administrative sanctions and criminal sanctions.